High-temperature-resistant wave-transparent aerogel composite material and preparation method thereof
By forming a dual network structure and uniformly distributing chromium oxide in the aerogel composite, the problem of uneven dielectric and thermal insulation properties of existing modified aerogels at high temperatures is solved, and the excellent dielectric and thermal insulation properties of composite materials at high temperatures are achieved.
Patent Information
- Application Number
- CN202411831632.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-21
AI Technical Summary
The existing modified aerogels have uneven dielectric and thermal insulation properties under high temperature environments, resulting in limited use of composite materials at high temperatures.
By mixing chromium chloride and propylene oxide with silica precursor solution, crosslinker solution and alkaline catalyst, an aerogel precursor solution with a dual network structure is formed. The solution is used to vacuum impregnate and supercritical dry the wave-permeable fibers, and finally calcinate at high temperature to form an aerogel composite material with uniform distribution of chromium oxide.
The aerogel composite material has excellent dielectric properties and thermal insulation properties under high temperature environments, with a dielectric loss tangent value below 5×10-3, and the thermal conductivity at 1000°C is 0.045-0.055 (W·m-1·K-1).
Smart Images

Figure BDA0005185687130000141 
Figure BDA0005185687130000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogel preparation, and in particular to a high-temperature resistant and wave-transmitting aerogel composite material and a preparation method thereof. Background Art
[0002] Aerogel is a new type of low-density nanoporous material, which is formed by the accumulation of silica nanoparticles. It has a three-dimensional network nanoporous structure, which can significantly reduce the solid thermal conductivity, gas thermal conductivity and convection heat transfer of the material. It is currently the solid material with the best thermal insulation performance. For example, the thermal conductivity of silica aerogel material at room temperature can be as low as 0.012 (W·m -1 ·K -1 ). High temperature resistant aerogels include alumina aerogel, zirconia aerogel, carbon aerogel and silica aerogel; among them, alumina, zirconia and silica aerogel can be used stably in an oxidizing atmosphere. However, based on the current research situation, researchers have not conducted in-depth research on the dielectric properties of aerogels, and there has been no extensive research on materials that have excellent dielectric properties and thermal insulation properties at high temperatures.
[0003] In the related art, the silica aerogel with excellent dielectric properties is usually modified and prepared. The traditional radiation-resistant aerogel is prepared by doping the radiation-resistant agent in the precursor solution by physical spraying or physical blending. After the sol-gel process, the radiation-resistant particles are confined in the silica aerogel nanonetwork, thereby achieving the purpose of radiation resistance. However, when the radiation-resistant agent is doped in this method, the radiation-resistant agent particles are prone to sedimentation during the sol-gel process, resulting in uneven dispersion of the radiation-resistant agent particles in the aerogel network, resulting in a density gradient in the composite material, which in turn makes the dielectric properties and thermal insulation properties of the composite material at high temperatures uneven.
[0004] Based on this, there is an urgent need to provide a high temperature resistant and wave-transparent aerogel composite material and a preparation method thereof. Summary of the invention
[0005] The embodiment of the present invention provides a high temperature resistant and wave-transmitting aerogel composite material and a preparation method thereof, which can solve the problem of uneven dielectric properties and thermal insulation properties of traditional modified aerogels in high temperature environments.
[0006] In a first aspect, the present invention provides a method for preparing a high temperature resistant and wave-transmitting aerogel composite material, the preparation method comprising the following steps:
[0007] (1) adding chromium chloride and propylene oxide into water and mixing them to obtain a chromium salt solution;
[0008] (2) stirring and mixing a silica precursor solution, a crosslinking agent solution, a chromium salt solution and an alkali catalyst to obtain a matrix aerogel precursor solution; wherein the crosslinking agent solution is a siloxane crosslinking agent solution;
[0009] (3) using the matrix aerogel precursor solution to vacuum impregnate the wave-transmitting fiber reinforcement, and then subjecting it to strengthening treatment and supercritical drying to obtain an aerogel composite material precursor;
[0010] (4) calcining the aerogel composite material precursor to obtain the high temperature resistant and wave-transmitting aerogel composite material.
[0011] Preferably, in step (2), the siloxane crosslinking agent solution is prepared by the following method:
[0012] (21) adding a siloxane reaction monomer and an acid catalyst to an organic solvent and mixing them, and obtaining a first reaction solution after a hydrolysis reaction; preferably, the siloxane reaction monomer is at least one of dimethyldiethoxy, dimethyldimethoxy, trimethylmethoxy, trimethylethoxy, methyltrimethoxy, methyltriethoxy, methylorthosilicate or ethylorthosilicate;
[0013] (22) adding a base catalyst to the first reaction solution to obtain a second reaction solution after a prepolymerization reaction;
[0014] (23) After vacuum drying the second reaction solution, a stabilizer is added and mixed to obtain the siloxane crosslinker solution; preferably, the stabilizer is a nonionic or anionic surfactant.
[0015] Preferably, in step (21), the mass ratio of the siloxane reaction monomer, the acid catalyst and the organic solvent is (20-30): (0.05-0.2): (70-80).
[0016] Preferably, in step (22), the mass ratio of the alkaline catalyst to the mixed solution is (0.5-2):100.
[0017] Preferably, in step (21), the temperature of the hydrolysis reaction is 50-90°C and the time is 0.5-2h;
[0018] In step (22), the prepolymerization reaction temperature is 40-50° C. and the time is 1-4 h;
[0019] In step (23), the vacuum drying temperature is ≯10° C., and the stabilizer accounts for 0.1-0.5 wt % in the siloxane crosslinking agent solution.
[0020] Preferably, in step (1), in the chromium salt solution, the content of chromium chloride is 1-50 parts, the content of propylene oxide is 1-5 parts, and the content of water is 1-90 parts, calculated by weight.
[0021] Preferably, in step (4), the calcination temperature is 550-1000° C., the heating rate is 8-12° C. / min, and the holding time is 1-5 h.
[0022] Preferably, the solute of the silicon dioxide precursor solution is an organic silicon sol, and the solvent is an organic solvent; wherein the content of the organic silicon sol is not more than 30 wt %.
[0023] More preferably, in the matrix aerogel precursor solution, by weight, the content of the silica precursor solution is 80-90 parts, the content of the crosslinker solution is 1-30 parts, the content of the chromium salt solution is 1-20 parts, and the content of the alkaline catalyst is 1-10 parts.
[0024] Preferably, in step (3), the wave-transmitting fiber reinforcement is alumina fiber, mullite fiber or quartz fiber; and the vacuum degree of the vacuum impregnation is -0.07 to 0.1 MPa.
[0025] More preferably, in step (3), the supercritical drying temperature is 40-50° C., the pressure is 13-15 MPa, and the heat and pressure holding time is 2-3 days.
[0026] Preferably, in step (3), before supercritical drying, the method further includes immersing the aerogel composite material precursor in a replacement solution and performing a strengthening treatment.
[0027] More preferably, the replacement solution is ethanol and an alkali catalyst; wherein the content of ethanol is 80-100%, and the content of the alkali catalyst is 0-20%.
[0028] Preferably, after step (4), the method further comprises the steps of soaking the calcined aerogel composite material precursor in a silane coupling agent solution and drying the aerogel composite material precursor in turn.
[0029] Preferably, the strengthening treatment is: subjecting the impregnated wave-transmitting fiber reinforcement or aerogel composite material precursor to air-drying, baking and secondary drying in sequence to obtain a strengthened aerogel material.
[0030] More preferably, the air-drying temperature is 10-40° C., and the time is 0-7 days, and the oven-drying temperature is 40-150° C., and the time is 0-7 days.
[0031] In a second aspect, the present invention provides a high temperature resistant and wave-transmitting aerogel composite material prepared by any preparation method of the first aspect.
[0032] Compared with the prior art, the present invention has at least the following beneficial effects:
[0033] In the present invention, chromium chloride and propylene oxide are first mixed to form a chromium salt aqueous solution, and then the chromium salt aqueous solution is mixed with a silicon dioxide precursor solution, an alkali catalyst and a siloxane crosslinking agent solution during the reaction process. The chromium salt aqueous solution can form a chromium hydroxide gel under the action of the alkali catalyst. At the same time, the chromium hydroxide gel and the silicon dioxide precursor solution can be crosslinked with each other under the action of the siloxane crosslinking agent, so as to form an aerogel precursor solution with a double network structure; the precursor solution is used to impregnate and supercritically dry a wave-transmitting fiber, so as to form an aerogel nanoporous material system with a double network structure; finally, high-temperature calcination is performed to sinter the chromium oxide particles in the nanopores of the aerogel and confine them in the nanopores of the silicon dioxide aerogel, so as to obtain an aerogel composite material in which chromium oxide is evenly distributed, and further each region of the aerogel composite material has excellent dielectric properties and thermal insulation properties under a high temperature environment. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] The embodiment of the present invention provides a method for preparing a high temperature resistant and wave-transmitting aerogel composite material, the preparation method comprising the following steps:
[0036] (1) adding chromium chloride and propylene oxide into water and mixing them to obtain a chromium salt solution;
[0037] (2) stirring and mixing a silica precursor solution, a crosslinking agent solution, a chromium salt solution and an alkali catalyst to obtain a matrix aerogel precursor solution; wherein the crosslinking agent solution is a siloxane crosslinking agent solution;
[0038] (3) using the matrix aerogel precursor solution to vacuum impregnate the wave-transmitting fiber reinforcement, and then subjecting it to strengthening treatment and supercritical drying to obtain an aerogel composite material precursor;
[0039] (4) calcining the aerogel composite material precursor to obtain the high temperature resistant and wave-transmitting aerogel composite material.
[0040] In the embodiment of the present invention, chromium chloride and propylene oxide are first mixed to form a chromium salt aqueous solution, and then the chromium salt aqueous solution is mixed with a silica precursor solution, an alkali catalyst and a siloxane crosslinking agent solution during the reaction process. The chromium salt aqueous solution can form a chromium hydroxide gel under the action of the alkali catalyst. At the same time, the chromium hydroxide gel and the silica precursor solution can be cross-linked with each other under the action of the siloxane crosslinking agent, thereby forming an aerogel precursor solution with a double network structure; the precursor solution is used to impregnate and supercritically dry the wave-transmitting fiber to form an aerogel nanoporous material system with a double network structure, and finally, after high-temperature calcination, the chromium oxide particles in the nanopores of the aerogel are sintered together and constrained in the nanopores of the silica aerogel, so that the chromium oxide can be evenly distributed in the aerogel composite material, so that each region of the aerogel composite material has excellent dielectric properties and thermal insulation properties under high temperature environment.
[0041] According to some preferred embodiments, in step (2), the siloxane crosslinking agent solution is prepared by the following method:
[0042] (21) adding a siloxane reaction monomer and an acid catalyst into an organic solvent and mixing them evenly, and obtaining a first reaction solution after a hydrolysis reaction;
[0043] (22) adding a base catalyst to the first reaction solution to obtain a second reaction solution after a prepolymerization reaction;
[0044] (23) After vacuum drying the second reaction solution, a stabilizer is added and mixed to obtain the siloxane crosslinking agent solution.
[0045] According to some preferred embodiments, preferably, the siloxane reaction monomer is at least one of dimethyldiethoxy, dimethyldimethoxy, trimethylmethoxy, trimethylethoxy, methyltrimethoxy, methyltriethoxy, methylorthosilicate or ethylorthosilicate; and the stabilizer is a nonionic or anionic surfactant.
[0046] In an embodiment of the present invention, the above-mentioned types of siloxanes are used as raw materials to react under the action of acid catalysts and base catalysts to obtain a self-made siloxane crosslinker solution, and the self-made crosslinker solution is mixed with a silica precursor solution and a chromium salt solution. In this way, the chromium salt sol and the silica sol can be fully crosslinked without affecting the sol-gel reaction of silica, and the temperature resistance of the aerogel composite material can be further enhanced.
[0047] Meanwhile, in the process of preparing the crosslinking agent solution, the siloxane is first fully hydrolyzed under the action of an acid catalyst, and then a base catalyst is added to initiate a polymerization reaction, so that the siloxanes can be fully polymerized, thereby forming a siloxane crosslinking agent solution with a suitable molecular weight. Finally, the reaction solution after the reaction is vacuum dried at a temperature below 10° C. When the residual amount of the solvent in the reaction system is 50%, the drying is stopped, and a stabilizer is added to the solution to terminate the polymerization reaction between the molecular chains, thereby obtaining a siloxane crosslinking agent solution with a suitable concentration.
[0048] It should be noted that, in the embodiments of the present invention, the acid catalyst may be acetic acid or other organic acid, inorganic acid, or ammonium fluoride solution; the base catalyst may be one or more mixed solutions of aqueous ammonia or organic amine solution; and the organic solvent may be at least one of ethanol or a mixture of water and ethanol or other organic solvents.
[0049] According to some preferred embodiments, in step (21), the mass ratio of the siloxane reaction monomer, the acid catalyst and the organic solvent is (20-30): (0.05-0.2): (70-80) (for example, it can be 20:0.05:70, 25:0.05:70, 30:0.05:70, 20:0.1:70, 20:0.1:80, 25:0.1:75, 30:0.05:70, 30:01:75 or 30:0.2:80); in step (22), the mass ratio of the base catalyst and the mixed solution is (0.5-2): 100 (for example, it can be 0.5:100, 1:100, 1.5:100 or 2:100).
[0050] In the embodiment of the present invention, during the preparation of the siloxane crosslinking agent solution, the mass ratio of the siloxane reaction monomer, the acid catalyst and the base catalyst is reasonably controlled, so that the siloxane reaction monomer can have a suitable reaction rate, which is conducive to the formation of a siloxane crosslinking agent solution with a suitable molecular chain length; it has been confirmed by the experiment of the present invention that if the content of the siloxane reaction monomer is too low, it is not conducive to the prepolymerization reaction between the siloxanes, and if the content of the siloxane reaction monomer is too much, the reaction rate between the siloxane reaction monomer molecules will be too fast, which is not conducive to achieving the controllability of the crosslinking agent solution preparation process.
[0051] According to some preferred embodiments, in step (21), the temperature of the hydrolysis reaction is 50-90°C (for example, 50°C, 60°C, 70°C, 80°C or 90°C), and the time is 0.5-2h (for example, 0.5h, 1h, 1.5h or 2h); in step (22), the temperature of the prepolymerization reaction is 40-50°C (for example, 40°C, 42°C, 45°C, 48°C or 50°C), and the time is 1-4h (for example, 1h, 2h, 3h or 4h); in step (23), the temperature of the vacuum drying is 5-10°C (for example, 5°C, 8°C or 10°C), and the proportion of the stabilizer in the siloxane crosslinking agent solution is 0.1-0.5wt% (for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt% or 0.5wt%).
[0052] In the embodiments of the present invention, on the basis of reasonably controlling the quality of the siloxane reaction monomer, the acid catalyst and the base catalyst, the temperature and time of the hydrolysis reaction and the prepolymerization reaction are further controlled, thereby further enhancing the controllability of the siloxane reaction process.
[0053] According to some preferred embodiments, in step (1), in the chromium salt solution, the content of chromium chloride is 1-50 parts (for example, 1 part, 5 parts, 10 parts, 20 parts, 30 parts, 40 parts or 50 parts), the content of propylene oxide is 1-5 parts (for example, 1 part, 2 parts, 3 parts, 4 parts or 5 parts), and the content of water is 1-90 parts (for example, 1 part, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 70 parts, 80 parts or 90 parts), by weight.
[0054] In the embodiment of the present invention, chromium chloride is used as the main raw material, and a certain amount of propylene oxide is added and stirred with water to form a chromium salt solution. When the chromium salt solution is mixed with a silica precursor solution and a crosslinking agent solution, the silica precursor solution can undergo a sol-gel reaction. At the same time, the chromium salt solution can react with the solvent in the silica precursor solution to form a chromium hydroxide gel. Under the action of the crosslinking agent, the silica gel can crosslink with the chromium hydroxide gel, thereby forming an aerogel nanoporous material system with a double network structure.
[0055] At the same time, the present invention experiments confirmed that the chromium salt solution prepared with appropriate contents of chromium chloride and propylene oxide is conducive to ensuring that the aerogel composite material has excellent dielectric properties and temperature resistance on the basis of good mechanical strength of the overall structure. For example, if the content of chromium chloride is too high, although it can enhance the radiation resistance of the aerogel composite material to a certain extent, it will lead to poor dielectric properties of the aerogel composite material, and the structure of the aerogel will collapse during the sintering process; and if the content of propylene oxide is too high, it will cause waste of the replacement solution in the subsequent replacement process, which increases the experimental cost.
[0056] According to some preferred embodiments, in step (4), the calcination temperature is 550-1000°C (for example, it can be 550°C, 600°C, 700°C, 800°C, 900°C or 1000°C), the heating rate is 8-12°C / min (for example, it can be 8°C / min, 9°C / min, 10°C / min, 11°C / min or 12°C / min), and the holding time is 1-5h (for example, it can be 1h, 2h, 3h, 4h or 5h).
[0057] In the embodiment of the present invention, by calcining the aerogel composite material precursor at the above temperature, the chromium hydroxide particles in the aerogel pores can undergo a crystal transformation to form chromium oxide particles under the above temperature environment, and the chromium oxide particles in the single pores of the aerogel can be sintered together and confined in the nanopores of the silica aerogel, so that each region of the aerogel composite material has excellent dielectric properties and thermal insulation properties in a high temperature environment.
[0058] According to some preferred embodiments, the solute of the silicon dioxide precursor solution is an organic silicon sol, and the solvent is an organic solvent; wherein the content of the organic silicon sol is not more than 30wt%;
[0059] In terms of mass fractions, in the matrix aerogel precursor solution, the content of the silica precursor solution is 80-90 parts (for example, it can be 80 parts, 82 parts, 85 parts, 88 parts or 90 parts), the content of the cross-linking agent solution is 1-30 parts (for example, it can be 1 part, 5 parts, 10 parts, 15 parts, 20 parts or 30 parts), the content of the chromium salt solution is 1-20 parts (for example, it can be 1 part, 5 parts, 10 parts, 15 parts or 20 parts), and the content of the alkaline catalyst is 1-10 parts (for example, it can be 1 part, 3 parts, 5 parts, 8 parts or 10 parts).
[0060] In an embodiment of the present invention, a silica precursor solution, a chromium salt solution, a crosslinking agent solution and an alkali catalyst with appropriate contents are stirred and mixed to prepare a matrix aerogel precursor solution, so that the chromium salt solution and the silica precursor solution can be fully crosslinked, which is conducive to preparing an aerogel composite material with uniform dielectric properties and heat-resistant and heat-insulating properties at high temperatures. It has been confirmed by experiments of the present invention that if the content of the crosslinking agent solution is too little, it is not conducive to ensuring the full crosslinking of the chromium salt precursor and the silica precursor, thereby affecting the uniformity of the dielectric properties and heat-insulating properties of the aerogel composite material, and if the content of the crosslinking agent solution is too much, the crosslinking agent solutions will be crosslinked with each other, thereby increasing the porosity of the aerogel composite material, and then reducing the temperature resistance of the aerogel composite material. Furthermore, if the content of the silica precursor solution is too little, it is not conducive to forming an aerogel composite material with good overall strength and thermal insulation performance. If the content of the silica precursor solution is too much, the chromium oxide particles cannot be evenly dispersed in the aerogel pores, which is not conducive to ensuring the overall good dielectric properties and temperature resistance of the aerogel composite material.
[0061] According to some preferred embodiments, in step (3), the wave-transmitting fiber reinforcement is alumina fiber, mullite fiber or quartz fiber; the vacuum degree of the vacuum impregnation is -0.07-0.1 MPa (for example, it can be -0.07 MPa, -0.08 MPa, -0.09 MPa or -0.1 MPa); the temperature of the supercritical drying is 40-50°C (for example, it can be 40°C, 42°C, 45°C, 48°C or 50°C), the pressure is 13-15 MPa (for example, it can be 13 MPa, 14 MPa or 15 MPa), and the heat and pressure holding time is 2-3 days (for example, it can be 2 days or 3 days).
[0062] In the embodiment of the present invention, in order to ensure that the aerogel composite material forms a specific structure, the wave-transmitting fiber reinforcement is first placed in a mold, and then the vacuum degree is controlled to impregnate the wave-transmitting fiber reinforcement in the mold with a matrix aerogel precursor solution, thereby ensuring a good impregnation efficiency, and the matrix aerogel precursor solution can fully undergo a sol-gel reaction during and after the impregnation process, and finally, the aerogel composite material precursor can be formed after supercritical drying.
[0063] According to some preferred embodiments, in step (3), before supercritical drying, the aerogel composite material precursor is also immersed in a displacement solution and subjected to a strengthening treatment; the displacement solution is ethanol and an alkali catalyst; wherein the ethanol content is 80-100% (for example, 80%, 90% or 100%), and the alkali catalyst content is 0-20% (for example, 1%, 5%, 10%, 15% or 20%).
[0064] In an embodiment of the present invention, a mold with a wave-transmitting fiber reinforcement that has been vacuum-impregnated with a matrix aerogel precursor solution is sequentially air-dried and oven-dried at room temperature, thereby enhancing the skeleton strength of the aerogel structure; further, the wave-transmitting fiber reinforcement after the strengthening treatment is placed in the above-mentioned type of displacement solution for displacement, which can, on the one hand, displace the moisture in the aerogel system, and on the other hand, further enhance the strength of the chromium hydroxide gel, thereby enabling the overall shrinkage rate of the aerogel during the sintering process to be lower, which is beneficial to ensuring the higher strength of the aerogel skeleton.
[0065] At the same time, in the embodiment of the present invention, by controlling the ethanol content and the alkali catalyst content in the replacement solution, it is beneficial to replace the moisture in the aerogel system and enhance the strength of the overall skeleton of the aerogel; if the content of the alkali catalyst is too high, it is theoretically beneficial to enhance the strength of the overall skeleton of the aerogel, but at the same time it will increase the difficulty of subsequent supercritical drying. Therefore, the content of the alkali catalyst in the embodiment of the present invention is preferably 10-20%.
[0066] According to some preferred embodiments, after step (4), the method further includes soaking the calcined aerogel composite material precursor in a silane coupling agent solution and drying the aerogel composite material precursor in turn.
[0067] In the embodiment of the present invention, the calcined aerogel composite material is immersed in a silane coupling agent for 1-96 hours and dried at 50-80° C., thereby enhancing the moisture-proof performance of the aerogel composite material.
[0068] According to some preferred embodiments, the strengthening treatment is: the impregnated wave-transmitting fiber reinforcement or aerogel composite material precursor is sequentially air-dried and baked to obtain a strengthened aerogel material; the air-drying temperature is 10-40°C (for example, it can be 10°C, 20°C, 30°C or 40°C), and the time is 0-7 days (for example, it can be 1 day, 2 days, 3 days, 4 days, 5 days, 6 days or 7 days), and the drying temperature is 40-150°C (for example, it can be 40°C, 50°C, 80°C, 100°C, 120°C or 150°C), and the time is 0-7 days (for example, it can be 1 day, 2 days, 3 days, 4 days, 5 days, 6 days or 7 days).
[0069] In the embodiment of the present invention, after the wave-transmitting fiber reinforcement is impregnated with the matrix aerogel precursor solution, it is subjected to a primary strengthening treatment, thereby enhancing the skeleton strength of the aerogel composite material. After the wave-transmitting fiber reinforcement after the strengthening treatment is impregnated with the replacement solution, a secondary strengthening treatment is performed, which is beneficial to further enhance the skeleton strength of the aerogel composite material.
[0070] An embodiment of the present invention also provides a high temperature resistant and wave-transmitting aerogel composite material prepared by any of the preparation methods described above.
[0071] By using the preparation method in the embodiment of the present invention, the radiation-resistant agent (chromium oxide) can be made uniform in size and evenly distributed in the pores of the aerogel, so that the aerogel composite material has excellent dielectric properties under high temperature conditions (1000°C), and the dielectric loss tangent value is always less than 5×10 -3 , has lower thermal conductivity under high temperature conditions, and the thermal conductivity coefficient at 1000°C is 0.045~0.055 (W·m -1 ·K -1 ).
[0072] In order to more clearly illustrate the technical solution and advantages of the present invention, a high temperature resistant and wave-transparent aerogel composite material and a preparation method thereof are described in detail below through several embodiments.
[0073] Embodiment 1:
[0074] Prepare siloxane crosslinker solution:
[0075] (21) adding 30 g of a siloxane reaction monomer (dimethyldiethoxy) and 0.05 g of an acid catalyst (acetic acid) to 70 g of an organic solvent (60 g of ethanol and 10 g of deionized water), stirring at 60 ° C. for 2 h to obtain a first reaction solution;
[0076] (22) Add 0.5 g of a base catalyst (ammonia solution) dropwise to the first reaction solution while stirring. After the addition is complete, react at 50° C. for 2 h to obtain a second reaction solution.
[0077] (23) vacuum drying the second reaction solution at 0° C., adding a stabilizer (polyethylene glycol) when the residual amount of the solvent in the reaction solution is 50%, and stirring at room temperature (25° C.) for 30 minutes to obtain a siloxane crosslinker solution; wherein the content of the stabilizer in the siloxane crosslinker solution is 0.2%;
[0078] (1) adding 15 g of chromium chloride and 1.2 g of propylene oxide to 85 g of deionized water and stirring to obtain a chromium salt solution;
[0079] (2) 80 g of a silica precursor solution (organic silica sol ethanol solution), 10 g of a siloxane crosslinker solution, 10 g of a chromium salt solution, and 2 g of an alkali catalyst (tetraethylammonium hydroxide solution) were stirred and mixed to obtain a matrix aerogel precursor solution;
[0080] (3) placing the wave-transmitting fiber reinforcement (silica fiber) into a mold, and impregnating the matrix aerogel precursor solution into the wave-transmitting fiber reinforcement by vacuum impregnation, with a vacuum degree of -0.08 MPa; then, placing the mold with the wave-transmitting fiber reinforcement impregnated with the matrix aerogel precursor solution at room temperature (25°C) for 3 days, and then placing the mold in a 60°C oven for 3 days to obtain a gelled wave-transmitting fiber reinforcement;
[0081] The gelled wave-transmitting fiber reinforcement was removed from the mold, soaked in a replacement solution (800 g of ethanol and 100 g of an alkali catalyst (ammonia solution)) for 8 days, and then placed in the mold; the mold with the wave-transmitting fiber reinforcement soaked in the replacement solution was placed at room temperature for 3 days, and then placed in a 60°C oven for 3 days; the above materials were removed from the mold and placed in a supercritical drying kettle, the temperature in the kettle was set to 50°C, the pressure was 14 MPa, and the heat and pressure retention time was 3 days to obtain an aerogel composite material precursor;
[0082] (4) placing the aerogel composite material precursor in a muffle furnace for calcination, heating the temperature to 600°C at 10°C / min and keeping it for 2h, then heating the temperature to 800°C at 6°C / min and keeping it for 2h;
[0083] The calcined aerogel composite material was immersed in a silane coupling agent solution for 48 hours and then placed in a 50° C. oven for drying to obtain a high temperature resistant and wave-transmitting aerogel composite material.
[0084] Embodiment 2:
[0085] Prepare siloxane crosslinker solution:
[0086] (21) adding 30 g of siloxane reaction monomer (methyl trimethoxy) and 0.1 g of acid catalyst (acetic acid) to 75 g of organic solvent (65 g of ethanol and 10 g of deionized water), stirring at 60 ° C. for 2 h to obtain a first reaction solution;
[0087] (22) 0.8 g of a base catalyst (tetraethylammonium hydroxide solution) was added dropwise to the first reaction solution while stirring. After the addition was completed, the mixture was reacted at 50° C. for 2 h to obtain a second reaction solution.
[0088] (23) vacuum drying the second reaction solution at 5° C., and when the residual amount of the solvent in the reaction solution is 50%, adding a stabilizer (polyacrylic acid), stirring at room temperature (25° C.) for 30 minutes to obtain a siloxane crosslinker solution; wherein the content of the stabilizer in the siloxane crosslinker solution is 0.1%;
[0089] (1) adding 20 g of chromium chloride and 1.0 g of propylene oxide to 80 g of deionized water and stirring to obtain a chromium salt solution;
[0090] (2) 85 g of a silica precursor solution (organic silica sol ethanol solution), 5 g of a siloxane crosslinker solution, 6 g of a chromium salt solution, and 4 g of an alkali catalyst (ammonium fluoride solution) were stirred and mixed to obtain a matrix aerogel precursor solution;
[0091] (3) placing the wave-transmitting fiber reinforcement (silicon dioxide fiber) into a mold, and impregnating the matrix aerogel precursor solution into the wave-transmitting fiber reinforcement by vacuum impregnation, with a vacuum degree of -0.01 MPa; then, placing the mold with the wave-transmitting fiber reinforcement impregnated with the matrix aerogel precursor solution at room temperature (25°C) for 3 days, and then placing the mold in a 60°C oven for 3 days to obtain a gelled wave-transmitting fiber reinforcement;
[0092] The gelled wave-transmitting fiber reinforcement was removed from the mold, soaked in a replacement solution (800 g of ethanol and 150 g of an alkali catalyst (aqueous ammonia solution)) for 8 days, and then placed in the mold; the mold with the wave-transmitting fiber reinforcement soaked in the replacement solution was placed at room temperature for 3 days, and then placed in a 60°C oven for 3 days; the above materials were removed from the mold, placed in a supercritical drying kettle, the temperature in the kettle was set to 50°C, the pressure was 14 MPa, and the heat and pressure retention time was 3 days to obtain an aerogel composite material precursor;
[0093] (4) placing the aerogel composite material precursor in a muffle furnace for calcination, heating the temperature to 600°C at 10°C / min and keeping it for 2h, then heating the temperature to 800°C at 6°C / min and keeping it for 2h;
[0094] The calcined aerogel composite material was immersed in a silane coupling agent solution for 72 hours and then placed in a 50° C. oven for drying to obtain a high temperature resistant and wave-transmitting aerogel composite material.
[0095] Embodiment 3:
[0096] Prepare siloxane crosslinker solution:
[0097] (21) adding 20 g of siloxane reaction monomer (methyl triethoxy) and 0.1 g of acid catalyst (dilute sulfuric acid) to 80 g of organic solvent (70 g of isopropanol and 10 g of deionized water), stirring at 60 ° C for 2 h to obtain a first reaction solution;
[0098] (22) Add 0.5 g of a base catalyst (tetraethylammonium hydroxide solution) dropwise to the first reaction solution while stirring. After the addition is complete, react at 50° C. for 2 h to obtain a second reaction solution.
[0099] (23) vacuum drying the second reaction solution at -5°C, adding a stabilizer (polyacrylic acid) when the residual amount of the solvent in the reaction solution is 50%, and stirring at room temperature (25°C) for 30 minutes to obtain a siloxane crosslinker solution; wherein the content of the stabilizer in the siloxane crosslinker solution is 0.2%;
[0100] (1) adding 40 g of chromium chloride and 3 g of propylene oxide to 60 g of deionized water and stirring to obtain a chromium salt solution;
[0101] (2) 80 g of a silica precursor solution (organic silica sol ethanol solution), 6 g of a siloxane crosslinking agent solution, 8 g of a chromium salt solution, and 5 g of an alkali catalyst (ammonium fluoride solution) were stirred and mixed to obtain a matrix aerogel precursor solution;
[0102] (3) placing the wave-transmitting fiber reinforcement (silica fiber) into a mold, and impregnating the matrix aerogel precursor solution into the wave-transmitting fiber reinforcement by vacuum impregnation, with a vacuum degree of -0.09 MPa; then, placing the mold with the wave-transmitting fiber reinforcement impregnated with the matrix aerogel precursor solution at room temperature (25°C) for 3 days, and then placing the mold in a 60°C oven for 3 days to obtain a gelled wave-transmitting fiber reinforcement;
[0103] The gelled wave-transmitting fiber reinforcement was removed from the mold, soaked in a replacement solution (800 g of ethanol and 200 g of an alkali catalyst (aqueous ammonia solution)) for 8 days, and then placed in the mold; the mold with the wave-transmitting fiber reinforcement soaked in the replacement solution was placed at room temperature for 3 days, and then placed in a 60°C oven for 3 days; the above materials were removed from the mold and placed in a supercritical drying kettle, the temperature in the kettle was set to 50°C, the pressure was 14 MPa, and the heat and pressure retention time was 3 days to obtain an aerogel composite material precursor;
[0104] (4) placing the aerogel composite material precursor in a muffle furnace for calcination, heating the temperature to 600°C at 10°C / min and keeping it for 2h, then heating the temperature to 800°C at 6°C / min and keeping it for 2h;
[0105] The calcined aerogel composite material was immersed in a silane coupling agent solution for 96 hours and then placed in a 50° C. oven for drying to obtain a high temperature resistant and wave-transmitting aerogel composite material.
[0106] Embodiment 4:
[0107] Example 4 is substantially the same as Example 1, except that in step (1), the mass of chromium chloride in the chromium salt solution is 60 parts.
[0108] Embodiment 5:
[0109] Example 5 is basically the same as Example 1, except that in step (2), the content of the silicon dioxide precursor solution is 100 g.
[0110] Embodiment 6:
[0111] Example 6 is basically the same as Example 1, except that in step (2), the content of the cross-linking agent solution is 40 g.
[0112] Embodiment 7:
[0113] Example 7 is substantially the same as Example 1, except that in step (3), the replacement solution comprises only 1000 g of ethanol.
[0114] Embodiment 8:
[0115] Example 8 is substantially the same as Example 1, except that in step (2), the crosslinking agent is 3-(trimethoxysilyl)propyl methacrylate of the same mass.
[0116] Comparative Example 1:
[0117] Comparative Example 1 is substantially the same as Example 1, except that in step (2), no crosslinking agent is added, and only 80 g of silica precursor solution (organic silica sol ethanol solution), 20 g of chromium salt solution and 2 g of alkaline catalyst (ammonium fluoride solution) are stirred and mixed to obtain a matrix aerogel precursor solution. Comparative Example 2:
[0118] Comparative Example 2 is basically the same as Example 1, except that in step (2), 85 g of silica precursor solution (organic silica sol ethanol solution), 5 g of siloxane crosslinker solution, 4 g of alkaline catalyst (ammonium fluoride solution) and 5 g of nano chromium oxide particles (commercially available) are stirred and mixed to obtain a matrix aerogel precursor solution.
[0119] Comparative Example 3:
[0120] Comparative Example 3 is substantially the same as Example 1, except that, in step (1), propylene oxide is not added in the preparation of the chromium salt solution.
[0121] The aerogel composite materials prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were subjected to performance tests. The test results are shown in Table 1.
[0122] Performance test method: The room temperature thermal conductivity is tested according to GB / T10295-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Heat Flow Meter Method", the high temperature (1000°C) thermal conductivity is tested according to YB4130-2005 "Test Method for Thermal Conductivity of Refractory Materials (Water Flow Plate Method)" standard, the dielectric constant and dielectric loss are tested according to Q / Hp 32-2012 "High-Cavity Test Method for Complex Dielectric Constant of Low-Loss Materials" standard, the density uniformity is tested according to GB / T6343-2009 "Determination of Apparent Density of Foam Plastics and Rubbers" standard, and the compression strength is tested according to GJB 10246.2-2021 "Test Method for Mechanical Properties of Fiber Reinforced Aerogel Insulation Materials Part 2: Compression Performance Test"; Temperature resistance test: The materials in the embodiment and the comparative example are respectively placed in a muffle furnace at the corresponding temperature, and the results obtained for 1800s are assessed. The shrinkage rate of length, width and height is required to be no more than 1%, and the temperature resistance temperature is determined.
[0123] Table 1
[0124]
[0125]
[0126] Note: “ / ” indicates that the performance cannot be tested;
[0127] As can be seen from Table 1, compared with the comparative example, the preparation method in the embodiment of the present invention can make the size of chromium oxide uniform and evenly distributed in the pores of the aerogel, so that the temperature resistance of the aerogel composite material can reach 1000°C, the density has good uniformity, and it has excellent dielectric properties under high temperature conditions (1000°C), and the dielectric loss tangent value is always less than 5×10 -3 , has lower thermal conductivity under high temperature conditions, and the thermal conductivity coefficient at 1000°C is 0.045~0.055 (W·m -1 ·K -1 ); In Example 4, the chromium content in the chromium salt solution is too much, so that the shrinkage rate of the composite material exceeds 50%, and defects such as delamination occur, and the performance cannot be tested; In Example 6, when the content of the cross-linking agent solution is too much, self-cross-linking occurs between the cross-linking agents, so that the silica precursor solution and the chromium salt solvent cannot be cross-linked to form a double network effect. At the same time, since the cross-linking agent itself has poor temperature resistance, if the cross-linking effect cannot be achieved, the temperature resistance of the composite material will be significantly reduced; In Example 8, the traditional cross-linking agent solution is used, so that the silica precursor solution and the chromium salt solvent cannot be fully cross-linked, and the temperature resistance of the composite material will be reduced.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high temperature resistant and wave-transmitting aerogel composite material, characterized in that: The preparation method comprises the following steps: (1) adding chromium chloride and propylene oxide into water and mixing them to obtain a chromium salt solution; (2) stirring and mixing a silica precursor solution, a crosslinking agent solution, a chromium salt solution and an alkali catalyst to obtain a matrix aerogel precursor solution; wherein the crosslinking agent solution is a siloxane crosslinking agent solution; (3) using the matrix aerogel precursor solution to vacuum impregnate the wave-transmitting fiber reinforcement, and then subjecting it to strengthening treatment and supercritical drying to obtain an aerogel composite material precursor; (4) calcining the aerogel composite material precursor to obtain the high temperature resistant and wave-transmitting aerogel composite material.
2. The preparation method according to claim 1, characterized in that: In step (2), the siloxane crosslinking agent solution is prepared by the following method: (21) adding a siloxane reaction monomer and an acid catalyst to an organic solvent and mixing them, and obtaining a first reaction solution after a hydrolysis reaction; preferably, the siloxane reaction monomer is at least one of dimethyldiethoxy, dimethyldimethoxy, trimethylmethoxy, trimethylethoxy, methyltrimethoxy, methyltriethoxy, methylorthosilicate or ethylorthosilicate; (22) adding a base catalyst to the first reaction solution to obtain a second reaction solution after a prepolymerization reaction; (23) After vacuum drying the second reaction solution, a stabilizer is added and mixed to obtain the siloxane crosslinker solution; preferably, the stabilizer is a nonionic or anionic surfactant.
3. The preparation method according to claim 2, characterized in that: In step (21), The mass ratio of the siloxane reaction monomer, the acid catalyst and the organic solvent is (20-30): (0.05-0.2): (70-80); and / or In step (22), the mass ratio of the alkaline catalyst to the mixed solution is (0.5-2):
100.
4. The preparation method according to claim 2, characterized in that: In step (21), the hydrolysis reaction temperature is 50-90°C and the time is 0.5-2h; In step (22), the prepolymerization reaction temperature is 40-50° C. and the time is 1-4 h; In step (23), the vacuum drying temperature is ≯10° C., and the stabilizer accounts for 0.1-0.5 wt % in the siloxane crosslinking agent solution.
5. The preparation method according to claim 1, characterized in that: In step (1), In the chromium salt solution, the content of chromium chloride is 1-50 parts, the content of propylene oxide is 1-5 parts, and the content of water is 1-90 parts, calculated by weight; and / or In step (4), the calcination temperature is 550-1000°C, the heating rate is 8-12°C / min, and the holding time is 1-5h.
6. The preparation method according to claim 1 or 2, characterized in that: The solute of the silicon dioxide precursor solution is an organic silicon sol, and the solvent is an organic solvent; wherein the content of the organic silicon sol is not more than 30wt%; and / or In the matrix aerogel precursor solution, by weight, the content of the silica precursor solution is 80-90 parts, the content of the crosslinking agent solution is 1-30 parts, the content of the chromium salt solution is 1-20 parts, and the content of the alkaline catalyst is 1-10 parts.
7. The preparation method according to claim 1, characterized in that: In step (3), The wave-transmitting fiber reinforcement is alumina fiber, mullite fiber or quartz fiber; the vacuum degree of the vacuum impregnation is -0.07--0.1MPa; and / or The supercritical drying temperature is 40-50° C., the pressure is 13-15 MPa, and the heat and pressure holding time is 2-3 days.
8. The preparation method according to claim 1, characterized in that: In step (3), before supercritical drying, the aerogel composite material precursor is immersed in a replacement solution and subjected to a strengthening treatment step; Preferably, the replacement solution is ethanol and an alkali catalyst; wherein the content of ethanol is 80-100%, and the content of the alkali catalyst is 0-20%; More preferably, after step (4), the method further comprises the steps of soaking the calcined aerogel composite material precursor in a silane coupling agent solution and drying the aerogel composite material precursor in turn.
9. The preparation method according to claim 1 or 8, characterized in that: The strengthening treatment comprises: drying and baking the impregnated wave-transmitting fiber reinforcement or aerogel composite material precursor in sequence to obtain a strengthened aerogel material; Preferably, the air-drying temperature is 10-40° C., and the time is 0-7 days, and the oven-drying temperature is 40-150° C., and the time is 0-7 days.
10. A high temperature resistant and wave-transmitting aerogel composite material, characterized in that: The preparation method is described in any one of claims 1 to 9.